A new species of Cerapus (Amphipoda: Senticaudata: Ischyroceridae) from Pulau Bum Bum, Sabah, Malaysia, with an identification key to Cerapus species - Nurshazwan, J.; Ahmad-Zaki, A.b.; Azman, B.a.r. (Zootaxa, 2020)
The first representative of the genus Cerapus in Malaysian waters, Cerapus bumbumiensis sp. nov. is described from specimens sampled from Pulau Bum Bum, Sabah (east Malaysia). The main identifying characteristics of this new amphipod species are: pereonites 1, 2 with constriction; male gnathopod 2 carpochelate, carpus large with long defining posterior tooth and well-developed anterodistal tooth; pereopod 6 coxa with fine hair/fringe setae ventrally; and telson with deep cleft. An updated identification key for the 23 known species in the genus is also presented.